Clinico-Pathological Study of Hysterectomy Specimens in Kathmandu Medical College Teaching Hospital - Pradhan, Sailesh Bahadur; Sedhain, Mamata; Acharya, Sneh; Maharjan, Sailuja; Regmi, Samikchhya (Birat Journal of Health Sciences, 2018)
Introduction: Uterus is subjected to many non-neoplastic and neoplastic diseases. Hysterectomy is the commonest gynecological surgery done for the management of the pathologies of the female reproductive system. Histopathological examination of hysterectomy specimens is done routinely which has both diagnostic and therapeutic significance. Objective: To study the common pathologies identified in hysterectomy specimens and to correlate them with the clinical findings. Methodology: A cross sectional study was carried out among all the hysterectomy specimens irrespective of primary lesion sent for histopathological examination from January 2016 to December 2017 in Department of Pathology, Kathmandu Medical College Teaching Hospital (KMCTH). Relevant history was taken from the requisition form. Ethical clearance was obtained from the Institutional Review Committee of KMCTH. Results: A total of 198 cases were studied. The most common pathology encountered was leiomyoma (60.0%) followed by adenomyosis (14.0%). Atrophic endometrium was seen in 24.3% cases. Chronic cervicitis was found in most of the cases (96.5%) along with endocervical polyp in 8.1% cases. Leiomyoma was found to be the most common indication for hysterectomy comprising 48.0% followed by abnormal uterine bleeding (24.75%) and utero-vaginal prolapse (18.25%). Hysterectomy was most commonly performed in the age group of 41 - 50 years and total abdominal hysterectomy with bilateral salpingo-oophorectomy was found to be the commonest procedure done comprising 8 0.0%. Conclusion: Leiomyoma was found to be the most common pathology in myometrium and chronic cervicitis in cervix. Abnormal uterine bleeding and vaginal prolapsed were also found to be common. Lesions which can be managed conservatively do need hysterectomy or not, is a matter of great concern. BJHS 2018;3(2)6:423-426.